Nickel hydroxide-based energy storage devices: nickel-metal hydride batteries vs. nickel hydroxide hybrid supercapacitors - Xuerui Yi; Caroline Kirk; Neil Robertson (Carbon Neutrality)
Abstract Nickel hydroxide-based devices, such as nickel hydroxide hybrid supercapacitors (Ni-HSCs) and nickel-metal hydride (Ni-MH) batteries, are important technologies in the electrochemical energy storage field due to their high energy density, long cycle life, and environmentally-friendliness. Ni-HSCs combine the high-power density of capacitors with the high energy density of batteries, making them ideal for applications requiring rapid charge and discharge cycles. In contrast, Ni-MH batteries are known for their high energy density and stability, making them suitable for applications requiring sustained energy output. Although Ni-MH batteries have been commercialized for many years and Ni-HSCs have also been extensively investigated as a relatively new technology, there is no comprehensive review comparing their performance and mechanisms. Therefore, this review aims to provide a detailed comparison of these two devices. This comparative study focuses on three perspectives: historic development; working principles; and properties of nickel hydroxide in both devices. This summary could offer insight into selecting appropriate technologies for specific applications, guidance for materials development and understanding the fundamental mechanism driving their performance.